An Investigation into Simile in Idioms a Contrastive Analysis Between English and Vietnamese - Nguyễn Thị Lệ Thu (2004)
Introduction; Literature review and theoretical background; Method and procedure; Linguistic and cultural features of similes in English and Vietnamese idioms; Conclusion and implications.